Excited State Dynamics of Odd [n]Cumulenes: Chain Length and Conformational Effects - Ullrich, Tobias; Sun, Bozheng; Yang, Yanwen; Schüßlbauer, Christoph; Ferguson, Michael J.; Fazzi, Daniele; Negri, Fabrizia; Tommasini, Matteo; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of the American Chemical Society, 2025)
Over the past decades, carbon allotropes have been extensively studied and applied to various technological applications due to their unique electronic and optical properties. Contemporary research has focused on quasi-1D, 2D, and 3D materials. On the other hand, the synthesis and isolation of carbyne as the 1D sp-hybridized carbon nanostructure remains elusive. Significant effort has been directed toward synthesis and study of carbon atomic wires (CAWs) as finite analogues of carbyne. The properties of CAWs composed of alkyne building blocks (oligoynes and polyynes) have provided glimpses of the potential properties of carbyne, while the synthesis and study of the alternative structure of CAWs, [n]cumulenes, remains in its infancy. Herein, we present an in-depth photophysical investigation of three odd [n]cumulenes (n = 3, 5, 7) assisted by quantum-chemical calculations. In contrast to the oligoynes, the photophysical properties of cumulenic carbon chains are dramatically impacted by both length and conformational effects of terminal end groups. We demonstrate how the subtle control over rotational motion with respect to the terminal CC bonds of cumulenes alters their electronic ground and excited states as well as dominating the photophysical deactivation cascade.
CRIS-Team Scopus Importer:2025-07-04